1978
DOI: 10.1128/aac.14.5.710
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Chlortetracycline on the Reservoir of Salmonella typhimurium in Experimentally Infected Swine

Abstract: Swine were fed either a diet containing 110 mg of chlortetracycline (CTC) per kg (100 g/ton) or a control diet and were inoculated orally with Salnonella typhimurium that was either susceptible or resistant to CTC. The quantity, duration, and prevalence of fecal elimination of S. typhimurium, as well as the effect of CTC on the transmission of S. typhimurium from infected to uninfected swine, were determined. When animals were infected with CTC-resistant S. typhimurium, CTC increased the quantity (P < 0.05), d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 12 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…In order for these simulated interventions to be of use, there needs to be a practical way in which such interventions can be implemented. Although it has been shown that adding antibiotics to feed can reduce the amount of Salmonella shed by an infected animal [34], with the presence of resistant Salmonella strains, the addition of the antibiotic to the resistant Salmonella strain can increase the quantity, duration and prevalence of faecal shedding [35]. Consequently, the use of antibiotics is somewhat controversial due to the potential increased risk of generating antimicrobial resistance, and therefore unlikely to be implemented in order to control Salmonella .…”
Section: Discussionmentioning
confidence: 99%
“…In order for these simulated interventions to be of use, there needs to be a practical way in which such interventions can be implemented. Although it has been shown that adding antibiotics to feed can reduce the amount of Salmonella shed by an infected animal [34], with the presence of resistant Salmonella strains, the addition of the antibiotic to the resistant Salmonella strain can increase the quantity, duration and prevalence of faecal shedding [35]. Consequently, the use of antibiotics is somewhat controversial due to the potential increased risk of generating antimicrobial resistance, and therefore unlikely to be implemented in order to control Salmonella .…”
Section: Discussionmentioning
confidence: 99%
“…Each group was composed of 5 swine and housed in a separate room. Each swine was confirmed to be Salmonella-free by a series of 3 rectal swab cultures [27]. The feed for both the LAhiST and LA-loST groups was a 2.8% DL-lactic acid (Musashino Nyuusan, Musashino Chemical Laboratory, Ltd., Tokyo, Japan) supplemented commercial corn-based grower feed (lactic acid added feed).…”
Section: Methodsmentioning
confidence: 99%
“…The number of ST116Rif r was transformed by using logarithms, where zero was interpreted as 1 organism per g of feces. A value of 100 organisms per g of feces was assigned to samples that were negative by direct plating methods but positive by the enrichment and delayed secondary enrichment procedures [27].…”
Section: Methodsmentioning
confidence: 99%
“…Previous research regarding Salmonella shedding and antimicrobial resistance subsequent to antimicrobial therapy has been conducted in laboratory facilities involving experimental infection with S. enterica. 1,4,9,10,16,18,21,23,26,27,38,53,54 This may not represent the typical subclinical Salmonella infections on swine farms, which often involve multiple serovars and variable time and dose of Salmonella exposure. 20,29 There are limited observational investigations that evaluated the impact of antimicrobial use on the antimicrobial resistance profiles between farms.…”
Section: Subtherapeutic Chlortetracycline and Salmonellamentioning
confidence: 97%